EVALUATING THE SAFETY OF RICE CULTIVARS VIA THE BIOACCUMULATION OF HEAVY METALS UNDER AGROCHEMICAL-INTENSIVE PRACTICES IN PHITSANULOK PROVINCE - Wachirawongsakorn, Piyada; Jamnongkan, Tongsai; Deetae, Natthinee (Life Sciences and Environment Journal, 2024)
The objectives of this research were to study the paddy soil properties and assess heavy metal contamination in paddy soil and rice grains in fields where five rice varieties, namely, RD41, RD49, RD51, RD79 and RD85 were cultivated. Paddy soil and rice grain samples were randomly collected from the same plots belonging to individual farmers, with three samples obtained for each rice variety, resulting in a total of 15 sample plots within Phitsanulok province. The heavy metal contents were quantified by using a flame atomic absorption spectrometer. The bioaccumulation factors of heavy metals in these rice varieties were subsequently evaluated. The results indicated that paddy soil exhibits a suitable soil texture and pH level, with adequate quantities of organic matter and potassium for rice cultivation. However, the nitrogen and phosphorus contents were presented in relatively low, necessitating soil quality improvement to enhance rice growth. Regarding heavy metal contamination in the paddy soil, these contamination levels did not exceed the specified standards. The contamination levels ranked as follows: Mn > Zn > Pb > Cu > Cd, with ranged between 76.35-240.88, 27.14-209.74, 1.70-28.11, 2.37-17.90, and 3.87-6.29 mg/kg, respectively. In terms of heavy metal contamination in rice grains, only the amount of Pb contamination in the RD41 rice variety was found to exceed the standard criteria announced by the Ministry of Public Health (≤0.2 mg/kg). Nevertheless, none of the rice varieties were classified as hyperaccumulators, as their Bioaccumulation Factors (BAF) consistently remained below 1.